2014
DOI: 10.1248/bpb.b13-00574
|View full text |Cite
|
Sign up to set email alerts
|

Different Effects of Epigenetic Modifiers on the Cytotoxicity Induced by 5-Fluorouracil, Irinotecan or Oxaliplatin in Colon Cancer Cells

Abstract: We investigated the effects of epigenetic modifiers such as DNA methyltransferase (DNMT) or histone deacetylase (HDAC) inhibitors on the cytotoxicity induced by 3 anticancer drugs (5-fluorouracil (5-FU), irinotecan (CPT-11) or its active form SN38, and oxaliplatin (L-OHP)) in human colorectal cancer (CRC) cells. Cytotoxicity in 4 CRC cell lines (HT29, SW480, SW48 and HCT116) was examined by colorimetric assay after drug treatment for 72 h. The effects of drug combinations were analyzed by an isobologram method… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(25 citation statements)
references
References 24 publications
1
24
0
Order By: Relevance
“…5-Aza-2'-deoxycytidine (DAC) is a DNA methyltransferase (DNMT) inhibitor, a DNA demethylating agent, and a cell cycle-arresting agent (7)(8)(9). Preliminary studies have been conducted on the combined use of DNMT inhibitors with existing antitumor agents (10)(11)(12). Accordingly, a preliminary experiment was conducted on a combination of a specific antitumor agents, including CPT-11, SN-38 or 5-FU with one of several epigenetic modifiers including DAC in two different human CRC cell lines; HCT116 and HT29 (13).…”
Section: Introductionmentioning
confidence: 99%
“…5-Aza-2'-deoxycytidine (DAC) is a DNA methyltransferase (DNMT) inhibitor, a DNA demethylating agent, and a cell cycle-arresting agent (7)(8)(9). Preliminary studies have been conducted on the combined use of DNMT inhibitors with existing antitumor agents (10)(11)(12). Accordingly, a preliminary experiment was conducted on a combination of a specific antitumor agents, including CPT-11, SN-38 or 5-FU with one of several epigenetic modifiers including DAC in two different human CRC cell lines; HCT116 and HT29 (13).…”
Section: Introductionmentioning
confidence: 99%
“…44 Regarding epi-drugs, it has been recently highlighted their capability (mostly HDACi and DNMTi) 45,46 to increase chromatin accessibility to conventional DNA-damaging chemotherapeutic agents, markedly enhancing their effects and establishing a rationale for their combination. Several pieces of evidence showed that the CpG island methylation is responsible for the induction of drug resistance, and this effect can be reversed through the treatment with hypomethylating agents [47][48][49][50] including zebularine 50 and decitabine 2. 50,51 The combination of HDACi with cytostatic agents (such as doxorubicin and paclitaxel) has been widely evaluated in both preclinical and clinical contexts.…”
Section: The Mmt Approachmentioning
confidence: 99%
“…Several pieces of evidence showed that the CpG island methylation is responsible for the induction of drug resistance, and this effect can be reversed through the treatment with hypomethylating agents [47][48][49][50] including zebularine 50 and decitabine 2. 50,51 The combination of HDACi with cytostatic agents (such as doxorubicin and paclitaxel) has been widely evaluated in both preclinical and clinical contexts. Here, a reliable increase in the therapeutic outcome was achieved, due to the downregulation of proangiogenic and tumorigenic factors (ie, hypoxia-inducible factor 1 [HIF-1α] and vascular endothelial growth factor [VEGF]), 52,53 the repression of DNA repair systems 54 as well as the enhancement of apoptosis induction.…”
Section: The Mmt Approachmentioning
confidence: 99%
See 1 more Smart Citation
“…All the experiments were carried out in triplicate. By the method of Chou and Talalay, [35][36][37] the combination indexes (CIs) isobologram were calculated and plot with Calcusyn software, and a CI value >1, CI value=1, and CI value <1 mean antagonism, additivity, or synergism, respectively.…”
Section: Mtt Assay and Examination Of Drug Combinationmentioning
confidence: 99%